Blended Learning in the Context of EFL: Curriculum Design and Implementation - Chang, Wan-Jeng (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2023)
This study proposed a curriculum design that thoroughly considers blended learning in the context of English as a foreign language (EFL). The main objectives were (1) to list the components to be included in the curriculum and how such components should be presented so that the curriculum can be successfully implemented and (2) to implement this curriculum in higher education. A total of 27 EFL students from a university in central Taiwan participated in the study. Various tasks were used to enable the students to actively explore the subject content and improve their language skills. Surveys and face-to-face meetings were also conducted to explore the students’ perspectives regarding the course, and the results of their feedback revealed their positive attitude toward the course. The educational activities, procedures, final results, and reflections regarding further research are explained herein. This study contributed to the field of EFL blended learning.